Do Maternal Interactive Behaviors Correlate With Developmental Outcomes and Mastery Motivation in Toddlers With and Without Motor Delay?. Issue 12 (1st December 2014) - Wang, Pei-Jung; Morgan, George A.; Hwang, Ai-Wen; Chen, Li-Chiou; Liao, Hua-Fang
Abstract : Background: Maternal interactive behaviors theoretically affect developmental outcomes and mastery motivation in young children. However, these associations are inconsistent in the literature. Objective: The purposes of this study were: (1) to examine the differences in maternal behaviors between toddlers with motor delay (MD) and those with typical development (TD), (2) to investigate the correlation of maternal behaviors and developmental quotients (DQs) in toddlers with MD and TD, and (3) to examine the correlation of maternal behaviors and mastery motivation in toddlers with MD and TD. Design: This was a sex- and mental age–matched case-control study. Methods: Twenty-two mother-child dyads of toddlers with MD (ages 23–47 months) and 22 dyads of sex- and mental age–matched toddlers with TD (ages 15–29 months) were recruited. Maternal scores from the Nursing Child Assessment Teaching Scale, 2 indicators of motivation (persistence and mastery pleasure) from individualized mastery tasks and the Dimensions of Mastery Questionnaire, and DQs from the Comprehensive Developmental Inventory for Infants and Children were assessed. Results: Mothers of children in the MD group showed significantly lower cognitive growth fostering scores than mothers of children in the TD group. Maternal total scores were significantly correlated with whole DQs in both groups. In the MD group, maternal total scores correlated significantly with DMQ mastery pleasure but not with mastery task motivation. Limitations: The study design makes it impossible to know the causal relationships between maternal behaviors and children's DQs and motivation. Conclusions: Mothers of toddlers with MD exhibited less adequate interactive behaviors than mothers of toddlers with TD. Because higher-quality maternal behaviors correlated with higher DQs in the MD group, clinicians should encourage parents to participate in early intervention programs and model high-quality parenting behavior to enhance parents' and children's outcomes.